Integrating Augmented Reality-Enhanced Simulations into Science Curriculum to Improve Conceptual Understanding in Middle School - Zulkifli Zulkifli; Noorthaibah Noorthaibah; Sumera Qureshi (International Forum of Researchers and Lecturers, 2024)
This study explores the integration of Augmented Reality (AR) simulations in middle school science education, focusing on improving students’ conceptual understanding of complex topics such as metamorphosis. The research adopts an experimental design with a treatment group using AR simulations and a control group utilizing traditional teaching methods. The study aims to determine the effectiveness of AR in enhancing students' engagement, motivation, and understanding, as well as to evaluate the perceptions of both students and teachers regarding its use in the classroom. Data is collected through pre-tests and post-tests to measure conceptual understanding, along with perception questionnaires to gather feedback on the AR learning experience. The results of this study are expected to reveal that students in the AR treatment group will demonstrate greater improvements in their conceptual understanding compared to those in the control group. Additionally, it is anticipated that both students and teachers will report positive feedback on the use of AR, citing its interactive and immersive nature as a key factor in boosting motivation and engagement. The study also addresses challenges such as access to technology, cost, and the need for teacher training in effectively integrating AR into the curriculum. The findings suggest that AR can significantly enhance science learning outcomes, making complex concepts more accessible and engaging. The study concludes with recommendations for schools to adopt AR technology, ensure teacher training, and invest in the necessary resources to support AR integration in the classroom. By doing so, AR can play a pivotal role in improving middle school science education.